Simulation of Single Stage Cascode Low Noise Amplifier at 5.8GHz Using T-Matching Network - Ibrahim , A.B; Othman, A.R; Husain , M.N; Johal, M.S (2011)
This paper presents a 5.8 GHz single stage cascode low noise amplifier using T-matching techniques for IEEE 802.16 standard. The amplifier use FHX76LP Low Noise SuperHEMT FET. The design simulation process is using Advance Design System (ADS) software. The cascode low noise amplifier (LNA) produced gain of 17.21dB and noise figure (NF) at 0.845dB. The input reflection (S11) and output return loss (S22) are -12.71dB and -15.52dB respectively. The bandwidth of the amplifier is 1GHz. The input sensitivity is complying with the IEEE 802.16 standards.